Prohexadiona cálcio no controle do crescimento vegetativo de pereiras - Pasa, Mateus da Silveira (2014)
Excessive vegetative growth is a major concern among pear growers because it results in serious negative effects in the orchard, such as increased pruning costs, shading of the inner parts of the canopy, poor fruit quality and difficult pest control. The use of plant growth regulators [e.g. Prohexadione calcium (PCa)] is one of the most promising techniques currently available to manage vegetative growth in pears. PCa reduces shoot growth by blocking the biosynthesis of the plant hormone gibberellin, which regulates longitudinal shoot growth. The aim of this study was, therefore, to evaluate the productive and vegetative responses of various pear cultivars to PCa. Three trials were carried out: Trial 1) PCa was applied to d Anjou pear trees in the lower and upper Hood River Valley, Oregon, USA to determine its effectiveness for managing the excessive vigor of d Anjou under different growing climates, with PCa rates ranging from 125 to 250 mg L-1. Ethephon was also applied (150 and 300 mg L-1) as an attempt to improve flower bud differentiation; Trial 2) PCa was selectively applied to dormant-headed (1/3rd removed) and unpruned shoots in a high-density d Anjou pear orchard in Oregon, USA. Both sets of shoots were treated with 250 mg L-1 P-Ca in either a single or double application; Trial 3) PCa was applied to Carrick , Packham s and William s pear in the experimental field of Federal University of Pelotas, RS, Brazil. Trees were treated with 750 g ha-1 i.a. PCa, which was split in four (187.5 g ha-1 a.i. each) and three timings (250 g ha-1 a.i. each) in the 2011 and 2012 growing seasons, respectively. The most important results are presented separated for each trial. Trial 1) P-Ca was effective for reducing shoot elongation at multiple sites over several growing seasons. In one case, the added benefits of increased fruit set and yield were also observed. However, the consistent reduction in return bloom and its translation to lower return yields, not previously documented for d Anjou , counteracts these benefits. Ethephon showed potential to ameliorate the activity of P-Ca on return bloom and production but it requires further investigation. Trial 2) At the end of the season, unpruned shoot length was decreased by 28% and 41% for shoots treated with P-Ca once and twice, respectively, while headed shoots were 37% shorter than their controls (treated only once). The number of nodes and average internode length were significantly reduced for P-Ca-treated shoots, irrespective of pruning level, conferring a higher node density relative to control shoots. These results implicate P-Ca as a powerful tool for precision-management of tree vigor in intensive pear plantings via selective treatment to areas of high vigor. Trial 3) The application of PCa at 750 g. ha-1 a.i satisfactorily controls shoot growth through the reduction of internode length of Carrick , Packham s and William s pears. Besides, it was observed that return bloom is not negatively affected by PCa. So, this plant growth regulator is a promissing management tool to reduce shoot growth and the need for pruning in pear orchards.